Council on Staff Affairs (COSA), Minutes, November 15, 2016 - Council on Staff Affairs, Valdosta State University (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 2016)
COSA, Minutes, November 2016.
1 electronic document. Council on Staff Affairs (COSA), Minutes, November 15, 2016. 2 pages.
Keywords: Council on Staff Affairs (Valdosta State University); Committees; Minutes (Records); Valdosta State University